INNOVATION OF BUSINESS LICENSING SERVICES IN ISSUING BUSINESS IDENTIFICATION NUMBERS (NIB) BASED ON E-GOVERNMENT THROUGH ONLINE SINGLE SUBMISSION (OSS) AT DPMPTSP PAMEKASAN - Mohammad Bustanol Husein; Dwi Reby Oktavia; Erina Saputri; Rina Nur Azizah (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This research aims to determine the realization of Business Licensing Service Innovation in the Issuance of E-Government Based Business Identification Numbers (NIB) through Online Single Submission (OSS) at the Pamekasan Regency One-Stop Integrated Service Capital Investment Service. The type of research used in this research is descriptive qualitative, where data is obtained from interviews and documentation. The data that the author has obtained is then analyzed using data analysis techniques from Miles and Hubberman, namely reducing data, presenting data, and verifying/drawing conclusions. This research uses the theory used by Everett M Rogers in Prabowo et al (2022) which is measured in several indicators, namely Relative Advantage, Compatibility, Triablity, Complexity, and Observability.).The results of this research show that the Business Licensing Service Innovation in Issuing Business Identification Numbers (NIB) Based on E-Government through Online Single Submission (OSS) at the Pamekasan Regency One-Stop Integrated Service Capital Investment Service can be said to be going well, although there are several problems However, this can be resolved by visiting the Pamekasan Regency DPMPTSP to get help with the problems you are experiencing. The increase in the number of NIB issuers every year shows that this innovation is in great demand by business people to help in processing business permits.